Using Lesson Study Model on Biology Microteaching for Improving Technology Pedagogy Content Islamic Knowledge - Herlanti*, Yanti; Fadlilah, Dina Rahma; Nobira, Shinji; Qumilaila, Qumilaila (Jurnal Pendidikan Sains Indonesia, 2024)
Microteaching is one of the crucial subjects to equip prospective teachers with technology pedagogy and content knowledge (TPCAK). In Islamic higher education institutions, TPACK is expanded to include technology pedagogy content islamic knowledge (TPCIK). This study explored the impact of the application of lesson study on micro-teaching on the ability of TPCIK from the aspect of cognitive knowledge, metacognitive attitude, and skills. The research method used a quasi-experimental non-equivalent control group. The research sample was Biology Education students who took micro-teaching courses, 19 in the control and 22 in the experimental classes. The instrument for measuring TPCIK used a test for assessing cognitive knowledge, self-assessment for assessing metacognitive attitude, and observation for assessing teaching skills. The results showed that TPCIK skills were seen from the self-assessment and observation results with a good average (value of more than 70), and there was no significant difference between the control and experimental groups. The result of the cognitive test is low, the average is less than 60, and there are differences between the control and experimental groups; in terms of knowledge, the group of students who applied the lesson study model is significantly better than the group using the conventional approach